1998
DOI: 10.1002/(sici)1097-0215(19980413)76:2<216::aid-ijc8>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of FHIT transcripts in cervical and endometrial cancers

Abstract: Carcinoma of the uterine cervix is a common malignancy, and many affected women, have been found to exhibit loss of heterozygosity (LOH) in the chromosome 3p region. Recent studies have localized the FHIT (fragile histidine triad) gene in this region and also demonstrated a high frequency of abnormalities of this gene in various cancers. To determine the role of the FHIT gene in cervical and uterine carcinomas, 16 cases of cervical carcinoma and 7 cases of endometrial carcinoma, as well as nearby non-cancerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The tissues were frozen immediately after surgical resection and stored in liquid nitrogen until extraction of either DNA or RNA. DNA extraction was performed as previously described [21,22]. Clinically, eight cases were stage I, 35 cases were stage II, eight cases were stage III, and two cases were stage IV.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissues were frozen immediately after surgical resection and stored in liquid nitrogen until extraction of either DNA or RNA. DNA extraction was performed as previously described [21,22]. Clinically, eight cases were stage I, 35 cases were stage II, eight cases were stage III, and two cases were stage IV.…”
Section: Samplesmentioning
confidence: 99%
“…Genomic DNA was modified with sodium bisulfite and methylation-specific PCRs were performed as described [21][22][23] with some modifications. Two pairs of primers for the promoter of each circadian gene were used to determine the methylation status of the promoter.…”
Section: Methylation-specific Pcr Analysis Of Circadian Genesmentioning
confidence: 99%
“…Inconsistent results were also obtained in the analysis of abnormal transcripts encoded by the fragile histidine triad (FHIT) gene at chromosome 3p14.2. These are also indicative of genomic instability (Sozzi et al, 1996) but the incidence reported varies from 30 to 80% in cervical cancer and 0 to 40% in normal tissue (Greenspan et al, 1997;Chu et al, 1998;Muller et al, 1998;Su et al, 1998;Yoshino et al, 1998;Nakagawa et al, 1999;Segawa et al, 1999). In only one study, which involved FHIT protein staining in 110 paraffin sections, was a reduction in FHIT gene expression observed to correlate with increasing lesion grade (Birrer et al, 1999).…”
mentioning
confidence: 99%
“…With only one exception all of the aberrant transcripts described here retain the sequences coded by exon 9, and it is perhaps of interest to note that aberrant FHIT transcripts from tumour types including ovarian, endometrial and cervical (Greenspan et al, 1997;Hendricks et al, 1997;Su et al, 1998), digestive tract (Chen et al, 1997), lung (Sozzi et al, 1996a;Fong et al, 1997), pancreatic (Simon et al, 1998), merkel cell carcinoma (Sozzi et al, 1996b), oesophageal (Michael et al, 1997), head and neck (Mao et al, 1996) and breast (Negrini et al, 1996) similarly retain exon 9 sequences in the aberrant transcripts. This may be particularly pertinent in the light of sequences present in this exon with high homology to the Kozaks translation initiation sequence (Kozak, 1984) and a small open reading frame, although as yet no peptide has been documented as arising from this site.…”
Section: Discussionmentioning
confidence: 86%